Multiple response optimisation of processing and formulation parameters of pH sensitive sustained release pellets of capecitabine for targeting colon. (3rd April 2018) - Pandey, Sonia; Swamy, S. M. Vijayendra; Gupta, Arti; Koli, Akshay; Patel, Swagat; Maulvi, Furqan; Vyas, Bhavin
Abstract: Purpose: To optimise the Eudragit/Surelease ® -coated pH-sensitive pellets for controlled and target drug delivery to the colon tissue and to avoid frequent high dosing and associated side effects which restrict its use in the colorectal-cancer therapy. Methods: The pellets were prepared using extrusion-spheronisation technique. Box–Behnken and 3 2 full factorial designs were applied to optimise the process parameters [extruder sieve size, spheroniser-speed, and spheroniser-time] and the coating levels [%w/v of Eudragit S100/Eudragit-L100 and Surelease ® ], respectively, to achieve the smooth optimised size pellets with sustained drug delivery without prior drug release in upper gastrointestinal tract (GIT). Results: The design proposed the optimised batch by selecting independent variables at; extruder sieve size ( X 1 = 1 mm), spheroniser speed ( X 2 = 900 revolutions per minute, rpm), and spheroniser time ( X 3 = 15 min) to achieve pellet size of 0.96 mm, aspect ratio of 0.98, and roundness 97.42%. The 16%w/v coating strength of Surelease ® and 13%w/v coating strength of Eudragit showed pH-dependent sustained release up to 22.35 h ( t 99% ). The organ distribution study showed the absence of the drug in the upper part of GIT tissue and the presence of high level of capecitabine in the caecum and colon tissue. Thus, the presence of Eudragit coat prevent the release of drug in stomach and the inner Surelease ® coat showed sustained drug release in the colon tissue. Conclusion: The study demonstrates the potential of optimised Eudragit/Surelease ® -coated capecitabine-pellets for effective colon-targeted delivery system to avoid frequent high dosing and associated systemic side effects of drug.